PEREMPUAN DALAM PUSARAN BUDAYA, POLITIK DAN KEKUASAAN MENAFSIR NARATIF DALAM 2 Samuel 3 – 6 HISTORIS KRISTIS, KRITIK FEMINIS, IDEOLOGI DALAM NARASI KISAH MIKHAL - Doys Ivone (IAKN Ambon, 2020)
The dialogue between snake and woman in Genesis 3: 1-6 is often understood as a form of human's inability to against the temptations of snakes which causes man's relationship with God to become distant. Even in some other dogmatic views, it is said that as a result of the fall, the